Green Marketing Communication as a Strategy for Sustainable Brand Image Formation at Maida Coffee - Viktorianus Mahendra Da Lopez; Yonas Ferdinand Riwu; Achwan Noorlistyo Adi (Dinasti Publisher, 2025)
This study examines the implementation of green marketing at Maida Coffee Shop, a local micro-business in Kupang, Indonesia, that has built a reputation for environmental concern despite its operational scale. The research addresses how the coffee shop integrates sustainability principles into its marketing and operational practices. Using a descriptive qualitative method, data were collected through in depth interviews with the owner and direct observation. The findings reveal that Maida Coffee actively constructs a green brand identity through strategic environmental communication, notably its